2019
DOI: 10.1055/a-1013-7686
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of Atremorine-Induced Neuroprotection and Dopamine Response in Parkinsonʼs Disease

Abstract: Atremorine is a novel bioproduct with neuroprotective effects on dopaminergic neurons and a natural L-DOPA donor in Parkinsonʼs disease (PD). In the present study, we show the effects of a single dose of Atremorine (5 g, p. o.) on plasma dopamine (DA) response and brain function in PD (n = 183) and the influence that pathogenic (LRRK2), metabolic (CYP2D5, CYP2C9, CYP2C19, CYP3A5, NAT2), transporter (ABCB1), pleiotropic (APOE), and detoxifying genes (CYP1B1, GSTT1, GSTP1, GSTM1, SOD2) involved in the pharmacoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(58 citation statements)
references
References 36 publications
0
58
0
Order By: Relevance
“…SNCA gene encodes the protein α-synuclein, now considered a central player in the pathogenesis of PD due to its aggregation into Lewy-bodies. SNP's in the SNCA gene are consistently linked to an increased risk of developing PD in GWAS studies in both familial and even sporadic PD [95]. In cases of autosomal dominant mutations, there is a solid L-dopa and classical PD treatment response, albeit with early cognitive and mental problems, akin to GBA mutations [108].…”
Section: Sncamentioning
confidence: 99%
“…SNCA gene encodes the protein α-synuclein, now considered a central player in the pathogenesis of PD due to its aggregation into Lewy-bodies. SNP's in the SNCA gene are consistently linked to an increased risk of developing PD in GWAS studies in both familial and even sporadic PD [95]. In cases of autosomal dominant mutations, there is a solid L-dopa and classical PD treatment response, albeit with early cognitive and mental problems, akin to GBA mutations [108].…”
Section: Sncamentioning
confidence: 99%
“…Of note that atremorine (E‐PodoFavalin‐1599929), a processed extract of V. faba with an increased L‐dopa concentration (2%, w/w), is proposed as dopaminergic neuroprotectant and L‐dopa donor (Cacabelos, 2016; Cacabelos et al, 2019). This substance has been tested in a small subset of Parkinson's patients with promising results (it could magnify the response of dopamine to conventional antiparkinsonian agents), but its clinical use is still premature (Cacabelos et al, 2016).…”
Section: Pharmacological and Biological Activities Of Vicia Plantsmentioning
confidence: 99%
“…In vivo studies showed that AtreMorine (i) protects against 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced dopaminergic neurodegeneration; (ii) inhibits MPTP-induced microglia activation and neurotoxicity in the substantia nigra; and (iii) improves motor function in mice with MPTP-induced neurodegeneration ( Figure 12) [62] (Table 7).…”
Section: Plant Biotechnology-related Productsmentioning
confidence: 99%
“…A recent study reported that AtreMorine-induced dopamine response is pharmacogenotype-specific and lasts from six to 12 hours, depending upon the pharmacogenetic profile of each patient (environmental factors, nutrition, and co-administration of different drugs may also modify this response). Genetic variants in pathogenic genes (APOE, LRRK2), metabolic genes (CYP2D6, CYP2C9, CYP3A5, NAT2) and detoxification genes (CYP1B1, GSTP1, SOD2) influence the response of dopamine to AtreMorine [65] (Table 7). Table 7.…”
Section: Plant Biotechnology-related Productsmentioning
confidence: 99%